Patents, knowledge creation, and spillovers in genetics for agriculture and natural resources - Samad, Ghulam, author; Graff, Gregory D., advisor; Maskus, Keith E., committee member; Weiler, Stephan, committee member; Hooten, Mevin, committee member (Colorado State University. Libraries, 2020)
Increasing food, energy, and resource demand by growing global population is putting unprecedented pressure on agriculture and natural resource systems. Innovation in agriculture, energy, and other resource intensive industries contributes enormously to productivity and sustainability gains. Innovation in genetic resources and biological systems is a particularly promising yet controversial area of such innovation. Generally, it has been observed that regional clustering (economies of agglomeration) plays an important role in driving innovation. To what extent do we observe regional clustering to play a role in innovation in these industries? Especially given that production is highly diffused geographically, and research and technology are seen as highly globalized (global public goods vs. global monopolies by MNCs). The overarching questions address by this study are the following: (1) What do patents reveal about geographic patterns of knowledge creation and spillovers? (2) What economic and policy factors drive invention activity at the regional scale? And indirectly, (3) What is the role of regional clustering in driving innovations for food security and sustainability? To address these overarching objectives this study is mainly separated into three parts. The first part delves into three related questions: (1) How have biological inventions for use in primary resource-intensive industries been spatially distributed across the United States? And, in particular, to what degree have they been geographically concentrated? (2) What are the time-space dynamics of biological inventions for these industries? To what extent does the concentration of previous inventions effect where new inventions arise? And, (3) based on these insights, can we identify primary innovation clusters in the U.S. for these industries? This study draws on detailed information on inventor address from about 34,000 patented inventions as indicators of innovation and entrepreneurship in three closely related industries: (1) agriculture, (2) bioenergy, and (3) environmental management. To address these questions three approaches are used mapping, Moran I and regression analysis. Results indicate these biological inventions are distributed across the U.S, but highly concentrated clusters are formed in urban regions. Moreover, a spatial clustering pattern clearly exists. In term of concentration of biological inventions for these industries, a rural-urban division exists. Inventions do not tend to concentrate near production activities but tend to concentrate in urban area. The number of inventions in an area in prior years has a significant impact on the number of current year inventions. This relationship represents the localized spillover phenomenon. While we do see inventions in rural areas, rural areas do not appear to be the hotspots of innovation in agricultural, energy, or environmental biotechnologies. The second part of this dissertation explores the covariates of regional concentration of these biological inventions for agriculture, energy, and environment in the United States. First, the geographic patterns of these inventions are analyzed using negative binomial panel regression of patented inventions by region, to identify the density of inventions overall as well as the space-time dynamics of invention cumulativeness. We find that inventions have been spatially concentrated in about 30 major metropolitan clusters, and that spatial distribution has remained remarkably stable over time. Factors of population, earnings, and farm income are correlated with their invention counts. As a first rule, these inventions are created in higher population urban regions. Although, among regions of similar population inventions are more likely closer to agricultural production. Results clearly show the emergence of largely urban innovation clusters in agriculture and resource industries. The third part of this dissertation broadens the scope to explore the spatial distribution and covariates of regional invention activity across Organization for Economic Cooperation and Development (OECD) countries. Three approaches are used mapping, Moran I and regression analysis to analyse the spatial distribution and covariates across OECD. The results showed that while inventions are distributed across the OECD, there again appear to be concentrated clusters in larger urban regions (another broader set of top 30 clusters). Moreover, the number of inventions made in prior years has significant explanatory power on the number of current year inventions, by region. This represents the localized spillover phenomenon. In addition, region size (as measured by population) and level of economic activity (as measured by regional income) do not appear to be related to the count of inventions for these industries. R&D expenditures (regional) and an IP index (which is national in nature but is applied to regions for this study) are strongly related to biotech invention activity for these industries. A rural-urban division does appear to exist. Finally, these invention counts appear to be negatively correlated with gross value added of agriculture by region across OECD countries.